2020
DOI: 10.1038/s41467-020-17564-z
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord injury causes chronic bone marrow failure

Abstract: Spinal cord injury (SCI) causes immune dysfunction, increasing the risk of infectious morbidity and mortality. Since bone marrow hematopoiesis is essential for proper immune function, we hypothesize that SCI disrupts bone marrow hematopoiesis. Indeed, SCI causes excessive proliferation of bone marrow hematopoietic stem and progenitor cells (HSPC), but these cells cannot leave the bone marrow, even after challenging the host with a potent inflammatory stimulus. Sequestration of HSPCs in bone marrow after SCI is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 83 publications
1
25
0
Order By: Relevance
“…Just how exactly bone marrow-derived immunity changes after SCI has been described in a few publications [ 86 , 87 , 88 ]. Clinically, persons with SCI exhibit impaired bone marrow stem cell function [ 86 , 87 ].…”
Section: Why Does Peripheral Immune Dysfunction Occur?mentioning
confidence: 99%
See 2 more Smart Citations
“…Just how exactly bone marrow-derived immunity changes after SCI has been described in a few publications [ 86 , 87 , 88 ]. Clinically, persons with SCI exhibit impaired bone marrow stem cell function [ 86 , 87 ].…”
Section: Why Does Peripheral Immune Dysfunction Occur?mentioning
confidence: 99%
“…When bone marrow aspirates were cultured, the number of long-term culture-initiating cells was significantly reduced in cultures from SCI persons, particularly tetraplegics, indicative of decreased progenitor growth [ 86 ]. Preclinically, a recent publication explored the mechanisms behind SCI-induced bone marrow hematopoietic dysfunction [ 88 ]. After SCI, mice exhibited increased hematopoietic stem cell proliferation and accumulation in the bone marrow, as well as impaired mobilization regardless of injury level and severity ( Figure 2 ).…”
Section: Why Does Peripheral Immune Dysfunction Occur?mentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism leading to B cell invasion into the spinal cord following SCI is currently unknown, although we show chemokine signaling may be involved. Intriguingly, other studies have shown lymphopoiesis is impaired in the bone marrow following SCI and B cells fail to mobilize 65 , suggesting B cells observed in the injured spinal cord might have a different origin. Indeed, recent studies suggest the meninges, cerebrospinal fluid, and vertebral bone may be a source of B cells entering the injured CNS [66][67][68][69] .…”
Section: Discussionmentioning
confidence: 86%
“…In particular, in MITO-Luc mice, high luciferase activity can be detected in spleen, testis, and bone marrow (vertebral column, sternum, femur), while non-proliferating tissues, such as lung, brain, heart, aorta, skeletal muscle, liver, and kidney, do not emit light under physiological conditions [ 27 ]. This experimental model has been instrumental in studies analyzing cell proliferation in response to hyperbilirubinemia [ 28 ], toxic insult [ 29 ], and ischemic [ 30 ] and spinal cord [ 31 ] injuries.…”
Section: Introductionmentioning
confidence: 99%